โครงการอนุรักษ์พันธุกรรมพืชอันเนื่องมาจากพระราชดำริ สมเด็จพระเทพรัตนราชสุดาฯ สยามบรมราชกุมารีสนองพระราชดำริโดยมหาวิทยาลัยเทคโนโลยีราชมงคลพระนคร (อพ.สธ. – มทร.พระนคร) - พีรพัชระ, จุฑามาศ (RMUTP Research Journal Sciences and Technology, 2014)
The ultimate goals of Plant Genetic Conservation Project Under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn are development of personnel and conservation and development of plant genetics resources for the advantages of Thai people. The objectives of this project are (1) to promote understanding and awareness of personnel and organization about the importance of plant genetic conservation; (2) to create links between various organizations, including government agencies and private sections on virtue foundation; and (3) to build a plant genetics database system that is accessible around the country. The master plan has been distributed over a period of five years. The current operations are in the fifth year of the plan. The operation had three frameworks and eight supporting activities that focused on three resource bases: physical resources, biological resources and cultural and wisdom resources. Rajamangala University of Technology Phra Nakhon (RMUTP) realizes the importance and the advantage of these resources. Thus, RMUTP has followed the royal initiation with several activities that supported the royal initiative since 2005. These projects were conducted within the frame of the master plan, with emphasis on utilization framework as well as establishment of good conscience.